Extensive Sodium Metal Plating and Stripping in a Highly Concentrated Inorganic−Organic Ionic Liquid Electrolyte through Surface Pretreatment. Issue 5 (26th April 2017) - Basile, Andrew; Makhlooghiazad, Faezeh; Yunis, Ruhamah; MacFarlane, Douglas R.; Forsyth, Maria; Howlett, Patrick C.
Abstract: The front cover artwork was designed by Dr. A. Basile. The image shows the abundance of sodium relative to other alkali metals, underscoring the recent shift toward sodium in energy storage research. Read the full text of the Communication at 10.1002/celc.201600784 . Abstract : "As part of a larger investigation funded by the Australian Research Council to investigate the fundamental operation of sodium‐ion and sodium‐metal energy storage technologies, a major focus of this investigation is an understanding of the formation of the solid‐electrolyte interphase, which is formed upon the electrodes when paired with novel electrolyte materials such as organic ionic plastic crystals or ionic liquids, particularly at high salt concentration…" Find out more about the story behind the front cover research at10.1002/celc.201600784 .